Thriving in the Political Sport Arena: LMX as a Mediator of the Political Skill– Career Success Relationship - Marshall Magnusen; Jun Woo Kim (Journal of Applied Sports Management, 2016)
Organizational politics, be it in sport organizations or other business contexts, is an unavoidable aspect of work and life. Further, some individuals are better than others at navigating the political arena and advancing their careers. It is therefore important to understand what characteristics those individuals possess and how exactly those characteristics lead to desirable career outcomes. This study progresses the organizational behavioral sciences forward by examining the mediation effects of leader-member exchange (LMX) in the relationships between intern political skill and four career-related outcomes (career satisfaction, perceived external marketability, life satisfaction, and perceived effectiveness). A total of 201 sport management student subjects were obtained. A boot-strapping method estimated with structural equation modeling (SEM) was used to test the mediation effects. The results of the study show that all the hypothesized mediation effects were indeed supported. Therefore, we concluded that the mediated paths of political skill through LMX to support career-success outcomes were supported. These results will hopefully stimulate continued interest in the individual “skills” and intervening ways through which aspiring sport professionals can achieve success in their internships (and subsequent employment) and current sport professionals can attain beneficial career-related outcomes.
Keywords: internship; interpersonal relationships; organizational politics; satisfaction; social effectiveness